Analysis of lens cloudiness during endoscopic submucosal dissection procedures: Effects of a novel lens cleaner - Takashi Fujii; Sho Watanabe; Misugi Uga; Yuuki Matsui; Kazuomi Sakaki; Naoki Matsukawa; Tomoyo Machida; Masamichi Kurihara; Yoshihiro Tashiro; Eiko Okamoto; Tsunehito Yauchi; Shinji Suzuki; et al. (DEN Open)
Abstract Objectives We aimed to identify independent factors for intraoperative endoscopic lens cloudiness during gastric and colorectal endoscopic submucosal dissections, investigate the effectiveness of Cleastay, an endoscope anti‐fog solution, and examine factors associated with severe submucosal fat deposition. Methods A total of 220 patients who underwent gastric or colorectal endoscopic submucosal dissections in two institutions between January 2022 and October 2023 were included. Significant factors related to cloudiness were determined using univariate and multivariate analyses. Patient background and tumor characteristics related to severe submucosal fat deposition were investigated, and the degree of intraoperative endoscopic lens cloudiness and outcomes were compared between the Cleash and Cleastay groups. Results In the multivariate analysis, factors increasing lens cloudiness included long procedure time (odds ratio [OR], 17.51; 95% confidence interval [CI], 1.52–202.08), stomach (vs. colon; OR, 5.08; 95% CI, 1.99–12.96), and severe submucosal fat deposition (OR, 12.19; 95% CI, 5.02–29.60). Conversely, the use of Cleastay (vs. Cleash; OR, 0.066; 95% CI, 0.021–0.21) was identified as a factor reducing cloudiness. Location analysis revealed that severe submucosal fat deposition was more common in the upper stomach and right colon. Conclusions It was suggested that Cleastay is more useful for endoscopic submucosal dissection of the upper stomach and right colon, where severe submucosal fat deposition is expected.